2015
DOI: 10.1111/oik.02216
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related variation and temporal patterns in the survival of a long‐lived scavenger

Abstract: Although senescence has been described for various fitness components in a wide range of animal species, few studies have studied senescence in long‐lived species, and little is known about its interactions with varying environmental conditions. Using a 32 year capture–mark–recapture dataset on the griffon vulture Gyps fulvus, we examined the demographic patterns of actuarial senescence and the patterns of year‐to‐year variation in survival rates. We found a significant, surprisingly late, decrease of annual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 91 publications
(147 reference statements)
1
31
2
Order By: Relevance
“…Importantly, female Egyptian vultures in our study population showed an alarmingly low local survival in comparison with the survival rates estimated for adults breeding in other European populations and other large body-sized scavengers83738. Higher rates of female mortality as that found here have been claimed as the main factor leading to male-skewed adult sex-ratios in many bird species with balanced sex-ratios at birt39.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Importantly, female Egyptian vultures in our study population showed an alarmingly low local survival in comparison with the survival rates estimated for adults breeding in other European populations and other large body-sized scavengers83738. Higher rates of female mortality as that found here have been claimed as the main factor leading to male-skewed adult sex-ratios in many bird species with balanced sex-ratios at birt39.…”
Section: Discussioncontrasting
confidence: 55%
“…Later in life, a decrease in survival (or reproductive success) at advanced ages (i.e., senescence9) was not detected for any sex. It is possible that the study period was relatively short with respect to the species’ potential longevity (captive birds survived up to 37 years22), or that sample size for very old individuals was small and senescence in long-lived birds has usually been detected very late in life821. It seems also reasonable that the relatively high rates of mortality of breeding adults detected here would preclude the appearance or detectability of senescence traits in our study population.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This suggested that factors compatible with IAH operate mainly at these scales, and excluded the possibility of food limitations predominating, as foraging ranges are larger than these scales and there was no support for the IAH at larger scales. Adverse weather conditions may force vultures to reduce their foraging area and concentrate foraging activity over fewer days (Monsarrat et al 2013), in addition to increased thermoregulation costs, which may affect survival and long-term fitness (Chantepie et al 2016). In territorial birds, as population density increases, an increasing proportion of animals are displaced into low-quality sites, leading to reduced fecundity or survivorship (Gill et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…even those of the lowest quality not used in other years, and the negative effect of rainfall. Adverse weather conditions may force vultures to reduce their foraging area and concentrate foraging activity over fewer days (Monsarrat et al 2013), in addition to increased thermoregulation costs, which may affect survival and long-term fitness (Chantepie et al 2016). Moreover, the presence of eyries in a cliff is a powerful attractant for conspecifics which use non-social cues for breeding (Erckmann et al 1990, Mateo-Tom as & Olea 2011.…”
Section: Discussionmentioning
confidence: 99%